Utilization of Antibacterial Substances from Lactic Acid Bacteria for Extension Shelf-life of Chilled Crab Meat - Mathana Sangjindavong; Jintata Limpakdee; Pongtep Wilaipun; Daungdoen Vareevanich (Agriculture and Natural Resources, 2006)
Six isolates screened from fifty samples of fermented fishery products including Pla-ra, Plasom, Pla-chao, Pla-chom and Kung-chom, were described as KPL-1, KPL-2, KPL-3, KPL-4, KPL-5 and KPL-6 and found to inhibit indicator organisms such as Lactobacillus plantarum ATCC 8041, Pediococcus pentosaceus ATCC 33316 and Listeria ivanovii DSM 4553, of which the KPL-4 isolate showed a maximum activity of 1,600 AU/ml. The six isolates were identified as Enterococcus faecalis based on morphological and biochemical characteristics. The antibacterial performance from the KPL-4 was decreased 50 percent by trypsin and pepsin, stable after heat treatment at 60°C for 15 min and 100°C for 30 min, while inactive at 121°C for 15 min. The molecular weight of the antibacterial compound was 3,800 dalton. The KPL-4 crude extracts of various concentrations including undiluted ones exhibited significant difference (P≤0.05) in reduction of total microorganisms as well as Listeria ivanovii in crab meat, with the 10% crude extracts showing most effective. Chilled crab meat treated with 10% crude extracts and kept for 10 days at 0°C had lower total viable count of bacteria than the untreated (P≤0.05) between treatments. Using antibacterial substances from lactic acid bacteria could decrease total viable count of bacteria and extend shelf-life of chilled crab meat for at least 10 days.